Staging the Obscene in A Glastonbury Romance (1932) by John Cowper Powys - Florence Marie (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2020)
A Glastonbury Romance by John Cowper Powys was published in 1932, just one year before the ban on James Joyce’s Ulysses was lifted in the United States. Powys’s novel was not censored, although it is rich in scenes and hints that would have been deemed obscene in the United Kingdom barely ten years before. This is probably due to the evolving mores of society in the 1930s but this is also a consequence of the tone used by Powys, which will enable me to draw a distinction between bawdiness and obscenity. Then the detailed analysis of two passages in which the abject and the sacred vie with each other will make it possible to highlight some characteristics of the staging of the obscene: scopic drives, a pre-symbolic relation with the world and a confrontation with a sense of reality that is so overwhelming that the sacred appears as the only answer—an answer which is both vain and necessary. Lastly, the article offers to probe into the position of the implied reader of obscene works thanks to the mise en abyme that can be found in the novel.